Gene editing of the thioester reductase step in the biosynthesis of lysergic acid amides - Lauren M. Bish; Jessica L. Fuss; Daniel G. Panaccione (PLoS ONE, 2025)
Ergot alkaloids derived from lysergic acid are important in agriculture, as food and feed contaminants, and in medicine, as the foundation of several pharmaceuticals. The fungus Metarhizium brunneum makes several lysergic acid amides, with lysergic acid α-hydroxyethylamide (LAH) being produced in by far the highest concentration. The multifunctional enzyme lysergyl peptide synthetase 3 (Lps3) has multiple domains that play important roles in lysergic acid amide synthesis. We hypothesized a role for the reductase domain of Lps3 in liberating LAH from an enzyme-bound precursor and tested this hypothesis with CRISPR/Cas9-based gene editing experiments. We transformed M. brunneum with a Cas9/single guide RNA complex and a donor DNA that replaced the tyrosine at the active site of the reductase domain of Lps3 with a phenylalanine. Sanger sequencing of edited and wild-type genes demonstrated successful editing of the reductase domain without non-target mutations in Lps3. High performance liquid chromatography of the edited strain showed a significant reduction of LAH and accumulation of the precursor lysergic acid. The phenotype was similar when the edited allele of lpsC was in a wild-type background or in backgrounds with late pathway genes easO or easP knocked out, except no LAH was detectable when the edit was in the easO knockout background. The data demonstrate that the reductase domain plays a key role or roles in formation of LAH. The abundant lysergic acid accumulating in the mutants, as opposed to later pathway intermediates in LAH biosynthesis (such as lysergyl-alanine), indicated severe debilitation of Lps3. The data indicate a requirement for the reductase domain of Lps3 in synthesis of lysergic acid amides and demonstrate the feasibility of the CRISPR/Cas9-based approach for editing genes in Metarhizium species.